Characterize Firewood and Charcoal Production and Marketing in Dry Lands of Ethiopia - Gonche Girma; Abebaw Shimeles (Journal of Development Economics and Digitalization, 2026)
The demand of woodfuel shows an increasing trend mainly in urban areas of Ethiopia due population growth, urbanization, poverty and unemployment. This causes diminishing of natural forest resources especially acacia tree species in drylands of the country. Therefore, the main aim of the study is to characterize the production and marketing system of woodfuel for sustainable demand and supply side management. Data were considered from primary and secondary sources. The primary data were collected mainly through household survey and through snowball sampling technique. A total of 245 households were interviewed who engaged in woodfuel production and trading in the drylands of Ethiopia. Findings indicate that charcoal producers (51.8%) and firewood collectors (28.9%) dominate the sector, with most households producing woodfuel year-round or during periods of cash need. Seasonal production is primarily driven by the need to supplement income, cope with shocks such as crop failure and livestock disease, and address household food shortages. The majority of woodfuel products are sold in nearby towns and villages, with fewer reaching regional and capital city markets. The study highlights the dual role of woodfuel production as a primary livelihood and an adaptive income source, underscoring the importance of sustainable production methods, improved market access, and policy interventions to enhance both economic and environmental outcomes. Keywords : charcoal; dryland; firewood; market; woodfuel   Abstrak Permintaan bahan bakar kayu menunjukkan tren peningkatan terutama di daerah perkotaan Ethiopia karena pertumbuhan penduduk, urbanisasi, kemiskinan, dan pengangguran. Hal ini menyebabkan berkurangnya sumber daya hutan alam terutama spesies pohon akasia di lahan kering negara ini. Oleh karena itu, tujuan utama dari penelitian ini adalah untuk mengkarakterisasi sistem produksi dan pemasaran bahan bakar kayu untuk manajemen sisi permintaan dan penawaran yang berkelanjutan. Data dipertimbangkan dari sumber primer dan sekunder. Data primer dikumpulkan terutama melalui survei rumah tangga dan melalui teknik pengambilan sampel bola salju. Sebanyak 245 rumah tangga diwawancarai yang terlibat dalam produksi dan perdagangan bahan bakar kayu di lahan kering Ethiopia. Temuan menunjukkan bahwa produsen arang (51,8%) dan pengumpul kayu bakar (28,9%) mendominasi sektor ini, dengan sebagian besar rumah tangga memproduksi bahan bakar kayu sepanjang tahun atau selama periode kebutuhan tunai. Produksi musiman terutama didorong oleh kebutuhan untuk menambah pendapatan, mengatasi guncangan seperti gagal panen dan penyakit ternak, dan mengatasi kekurangan pangan rumah tangga. Sebagian besar produk bahan bakar kayu dijual di kota-kota dan desa terdekat, dengan lebih sedikit yang mencapai pasar regional dan ibu kota. Studi ini menyoroti peran ganda produksi bahan bakar kayu sebagai mata pencaharian utama dan sumber pendapatan adaptif, menggarisbawahi pentingnya metode produksi berkelanjutan, peningkatan akses pasar, dan intervensi kebijakan untuk meningkatkan hasil ekonomi dan lingkungan. Keywords : arang; lahan kering; kayu bakar; pasar; bahan bakar kayu